Pat(now) = 24
24 = 2 * chris(some years before ) ' Pat is twice as old as Chris was
chris(some years before ) = 12
Chris(now) = 12 + x ' x years Later
pat(some years before) = Chris(now) ' Pat was as old as Chris is now
Pat(some years before) = Pat(now) - x ' x years Before
Pat(some years before) = 24 - x
Chris(now) = 24 - x 'Using the 5th Line
Chris(now) = 12 + x 'Using the 4th Line
24 - x = 12 + x
2x = 12 : x = 6
substituting the value of x in Chris(now) = 12 + x => 18
Chris = 18
Look at the following sentence... "chris(some years before ) = 12".
My First Doubt is how you assign the value 12....Because Pat age is 24 now only..Not some years before.....
Look at the following sentence... Pat is twice as old as Chris was when Pat was as old as Chris is now
OK your answer is 18. we substitude one by one for the above sentence..
First " When pat was as old as Chris is now". So at that time pat age is 18.
Second "Pat is twice as old as Chris" So at that time Chris age is 9, then only his age is 18.
Now pat age is 24..so the difference of years is 6.
So Chris age + 6 = 15...
But your answer is 18...
How you got it? can you explain.....
Suresh,
i guess you have misinterpreted that sentence.. i will make it little easier for you.
"Pat is twice as old as Chris was" => Pat(now)= (24/2)= chris(some years before).. This sentence is little tricky.If you understand this sentence correctly.. you can have 2 possibilities..
lets say for ex:- pat can be younger or older to chris.."Pat is twice as old as Chris was" because..
if some years before chris was 6 pat is now 12..=> but they have given another point that pat is 24.. that indicates that pat is older to chris.. so.. calculating accordingly as i have in my previous answer.... taking the value of Pat.. i found the answer...
ok but we have another line
1. Pat is twice as old as Chris was
2.when Pat was as old as Chris is now
u exlpained for 1st only . what about second it confuses to me .
tell about 2nd one
It looks like you people still have confusion in this problem. The following statement is a tricky one,
Pat is twice as old as Chris was when Pat was as old as Chris is now
let us assume that Pat's current age is P and Crish age is C and difference between P and C is D. As per the above statement,
age of Crish when Pat's age was C is half of the current age of Pat (that is P). When Pat's age was C Crish age was C - D (since difference between their age is D)
i-e) P = 2 ( C - D)
and P = C + D
Let Present ages be
Pat = P ; Chris = C
No years we are talking in past = 'x'
Previous Ages
Pat = P - x ; Chris = C - x;
Pat is twice as (P) as old as Chris WAS (c-x)
hence
P= 2(C-x)
when Pat was(P-x) as old as Chris is now(C)
hence
P-x = C
Solving,
x=6
Let present age of Chris=x
We know present age of Pat=24
Earlier Age t yrs earlier Present Age
Chris=x-t Chris=x
Pat=x Pat=24
Pat is twice as old as Chris was
when Pat was as old as Chris is now.
So,
24=2(x-t)…………………….(1)
x+t=24…………………………(2)
solving these simultaneously we get, x=18
Wat everyone(including me in my 1st attempt) were doing, were solving this question:- Pat was twice as old as Chris was
when Pat was as old as Chris is now.
Check out the words in red carefully.
I hope this may help those, who r still nt clear.